RANCANG BANGUN ALAT MONITORING TEMPOROMANDIBULAR DISORDER BERSIFAT NON-INVASIVE MENGGUNAKAN SENSOR ELEKTROMIOGRAFI (EMG) DILENGKAPI APLIKASI PEMANTAUAN PADA SMARTPHONE - Akbar, Handal Wally; Nurussa’adah, n/a; Ambarwati, Rusmi (Jurnal Mahasiswa TEUB, 2025)
Temporomandibular disorders (TMD) are characterized by craniofacial pain involving the joints, masticatory muscles, or muscles that innervate the head and neck. TMD can significantly reduce a person's quality of life such as eating and speaking, as well as affect the growth and development of the jaw and face. The main goals of TMD patient management are to reduce pain, reduce functional and parafunctional activities that cause abnormalities, and improve normal function. However, the lack of non invasive tools to measure the condition of muscle activity that parameterizes the severity of TMD is still a problem that exists today. Through this problem, a technology is needed that can monitor masseter and temporalis muscle activity by utilizing Electromyography sensors that can be connected to a monitoring application. The required technology can also provide classification of TMD severity conditions of patients using the asymmetry index method. This innovation has tested the functionality of the tool which is compared with the doctor's diagnosis. The results of data transmission tests via the internet with two different Access Point Bands were obtained with an average delivery time of 1.73 and 1.99 seconds. In testing the classification of conditions using the application obtained an accuracy rate of 100%. Testing the classification of conditions using the asymmetry index resulted in an accuracy rate of 86.67% by testing fifteen patients who have been diagnosed with TMD by doctors and normal patients.Keywords: Temporomandibular Disorder, Electromyography, Monitoring, Asymmetry index, Noninvasive